CGIAR Research Program on Water, Land and Ecosystems - Plan of Work and Budget 2021 - CGIAR Research Program on Water, Land and Ecosystems (CGIAR Research Program on Water, Land and Ecosystems, 2021)
Led by the International Water Management Institute (IWMI), WLE is a collaboration between CGIAR Research Centers, the Food and Agriculture Organization of the United Nations (FAO), the RUAF Foundation, and several national, regional and international partners. Through these partners, we provide evidence and solutions on natural resource management to influence key decision makers, including governments, international development organizations and financiers.